Through France with Berzelius : live scholars and dead volcanoes - Bernhard, Carl Gustaf (Pergamon Press, 1989)
There are 165 years between J & ouml;ns Jacob Berzelius' and Carl Gustaf Bernhard's excursions through the Massif Central in France. In spite of their circumstantial differences, the similarities between the two men of letters is striking. While Berzelius is renowned as one of the founders of modern chemistry and mineralogy, the bulk of Bernhard's achievement has been in the field of neurophysiology--yet both men emerge as having remarkably similar approaches to science and nature. It was as Berzelius' successor to the post of Secretary of the Royal Swedish Academy of Sciences that first gave Bernhard cause to study his literary remains. This was to provide the inspiration for Bernhard, with Berzelius as his guide, to visit the volcanic landscape, in which the remains of Roman columns, mediaeval castles and cathedrals recalled civilizations which have come and gone through the centuries following the geological eruptions. The book is extensively illustrated with sketches of the countryside, portraits of those known by Berzelius as well as colour photographs of the landscape taken by Bernhard, while the narrative alternates between excerpts of Berzelius' letters and writings and Bernhard's own modern travelogue. The result is a fascinating textual and pictorial record of one of the most beautiful regions of France, and of two highly influential Swedish scientists, spanning the last two centuries.